Consumer behavior change during the biometric payment technology implementation - l. G. Akhmaeva (Вестник университета)
A money evolution is going from classical payment form for goods and services to biometric ones last years. When companies introduce new biometric technologies, it is relevant to study a consumer readiness for the new payment system. This subject is new, studied and revealed still insufficiently in the scientific literature. The purpose of the article is to identify the existing biometric formats, the advantages and disadvantages of shopping by this way. Based on a scientific and Internet information sources the review and analysis of the activities of large Russian and foreign companies, providing the biometric payment service, on examples its implementation in retail and banking, are carried out. A comparative analysis of purchases at cash desks with a cashier, self-service cash desks and by biometric, is performed. The difficulties, which appear in switching from physical means to a biometric profile, and the technology limitations, are noted. The study recommends that companies and their partners and retailers, promoting the biometric payment, should inform consumers more to motivate them to use this method when shopping.